Assessing the chemical ecology and shelter-seaking behaviour of the grainchinch bug, Macchiademus diplopterus (hemiptera: lygaeidae) for optimisation of trapping during aestivation - Ngadze, Masimbaashe (Stellenbosch : Stellenbosch University, 2016)
Thesis (MScAgri)--Stellenbosch University, 2016.